Demystified ... the polymerase chain reaction. Issue 1 (1st February 1999) - Baumforth, K R; Nelson, P N; Digby, J E; O'Neil, J D; Murray, P G
Abstract : Since its initial description over twenty years ago the PCR has become one of the most valuable and flexible tools available to biomedical research. Subsequently, refinements and modifications to the basic approach, many of which have been described in this review, have enabled the application of the PCR to many areas of diagnostic medicine and have ensured its rapid acceptance as a routine test in many pathology disciplines. The growing importance of molecular approaches to the diagnosis of disease, particularly in histopathology, will continue to secure an ever expanding role for the PCR in diagnostic pathology.